Analisis Distribusi Termal Model Tabung Rheology Test Apparatus Sebagai Media Pengujian Ultrafine Bubbles (UFBs) - Nopriani, Meti Eliza; Puspawan, Angky; Witanto, Yovan; Budiman, Arif Adtyas (Jurnal Teknik Mesin, 2025)
The Fukushima Daiichi nuclear reactor accident has become a major concern in the development of safety design for advanced nuclear reactors. The reactor coolant system is part of the passive safety system, including the containment or reactor building cooling system. This system is designed to prevent damage to the reactor vessel structure and concrete building materials due to excessive heat release into the environment. The coolant flow is designed to move naturally without the help of a pump, utilizing the difference in fluid density as the main driver. The type of coolant plays a major role in generating the flow, especially in terms of its density properties. Fluids with a lower density than water can produce faster flow. One method to reduce the density of water is to insert fine bubbles known as ultrafine bubbles (UFB). To study the thermal characteristics of the fluid when heated, the Rheology Test Apparatus device is used. This study specifically examines the Rheology tube model. Analysis of temperature distribution in the tube is carried out using Computational Fluid Dynamics (CFD) simulations to understand the heat transfer mechanism. The validation process was carried out through experiments at a fluid temperature of 90°C, with a comparison of the temperatures at two points in the height of the tube, namely 0.16m and 0.8m, which are the locations of the heater and show the highest temperature.